Mitigating reflections in integrated gas sensors - Torres-Cubillo, Antonia; Wanguemert-Pérez, Juan Gonzalo; Sánchez-Postigo, Alejandro; Molina-Fernández, Íñigo; Halir, Robert (My University, 2022)
Optical gas sensing for environmental monitoring has become an active research topic in the last decade. Among the different optical sensing configurations, silicon photonic integrated sensors stand as a compact, CMOS-compatible alternative. However, even small on-chip reflections can create significant fringes when the optical path length is varied, e.g., when the wavelength is swept for TDLAS-like measurements. These fringes can be critical for NIR sensors, as absorption signals are much weaker in this region than in the MIR. Here, we propose a signal-processing method based on minimum phase techniques: by increasing the measurement bandwidth to around 2 nm we can completely remove the reflection artifacts through processing.
Keywords: Detectores ópticos - Congresos; Detectores de gases - Congresos; Óptica electrónica - Congresos; Silicon photonics; Gas sensing; Reflections